Estrus synchronization of native buffaloes using PGF2α and GnRH based protocols in Bangladesh (Bangladesh Journal of Livestock Research, 2021)
The inherent low reproductive efficiency of buffalo results in lower productivity. In buffalo overt signs of estrus are not as pronounced as in cattle, which hinders the reproductive efficiency of this species. The purpose of this study was to evaluate the effectiveness of GnRH and PGF2α-based estrus synchronization procedures in native buffaloes. About 16 indigenous buffaloes were equally grouped into two and treated with GnRH and PGF2α. In the GnRH-based treatment group of eight (8) buffaloes, the 1st 5ml GnRH injection was administrated initially (Day 15). Nine (09) days after the administration of the 1st GnRH injection, 5ml PGF2α was injected (Day 6) which was followed by the 2nd 5ml GnRH injection two (02) days after PGF2α administration (Day 4). In the case of PGF2α treated group, an initial injection of 5ml PGF2α was administrated to initiate the synchronization process (Day 15) which was followed by the 2nd injection of 5ml of PGF2α 12 days after the administration of 1st PGF2α injection (Day 4). In the GnRH-based treatment group, all buffalo cows (n=8) were inseminated artificially 16 hours after the last GnRH administration. In the PGF2α treated group, buffaloes (n=8) were inseminated artificially 90 hours after the last PGF2α administration. Visual monitoring of estrus signs and rectal examination during AI were used to determine the estrus response rate. All buffaloes were examined rectally for confirmation of pregnancy at 60 days post-insemination. Non-significant differences (p>0.05) were found between GnRH and PGF2α treated group in terms of responses of estrus synchronization (75% vs. 62.5%) and conception rate (37.5% vs. 25%) respectively. In conclusion, both the GnRH and PGF2α based protocols could be used to synchronize the estrus of indigenous buffaloes in Bangladesh.Bang. J. Livs. Res. Vol. 28 (1&2), 2021: P. 50-60